Manejo del complejo de hongos que causan Damping-off en los cultivos hortícolas - Lindao Vera, Reynaldo Cristóbal (2021)
The document was developed with the purpose of compiling information regarding the management of the complex of fungi that cause Damping-off in horticultural crops, which are crops with the greatest phytosanitary problems, since diseases constitute a limiting factor in their production. The pathogenic diseases that are present in seedlings is Damping-off, which causes rot when the root germinates before the cotyledons emerge or when the plant is emerged causes necrosis or injury at the base of the stem. Disease control is fundamentally based on the use of organic-synthetic fungicides. Therefore, it was determined that the greatest effectiveness of Damping-off control is obtained with biological products, such as Trichoderma harzianum in doses of 1.0 L / ha and pure plant extracts, because the vegetables show better agronomic behavior as height. of plant, number of leaves, greater root development, yield and consequently greater economic utility; there are biofungicides and chemical fungicides that increase the control of pathogens that cause stalk disease, despite the fact that chemical fungicides cause environmental deterioration; The causal agent of Damping-off in cabbages is Fusarium spp., which must be controlled with biological products, which are the ones that have given the best results in terms of plant height and vigor, compared to applications with chemical products and the Tomato crop is the vegetable most susceptible to Damping-off attack, caused by a complex of soil fungi Pythium sp., Fusarium sp. and Rhizoctonia solani that cause strangulation at the base of the stem.